Identifikasi Kebutuhan Tenaga Kerja Berbasis Pengabdian di Divisi Kapal Perang PT. PAL Indonesia - Ranum Sari, Amira; Wikartika, Ira (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Identifying workforce needs is very important to ensure that the company has the appropriate quantity and quality of workforce to support the smooth operation and achievement of organizational goals. PT PAL Indonesia, as a strategic company in the maritime industry, is committed to enhancing the effectiveness of human resource planning to support smooth operations, especially in the Warship Division. This identification process is carried out as part of a continuous evaluation, ensuring the alignment between the available workforce and the actual needs. The company applies a manpower planning and workload analysis-based approach to achieve these goals. With proper implementation, PT PAL Indonesia is expected to improve the efficiency of human resource management and ensure optimal operational continuity across all production lines, particularly in the Warship Division. Budget constraints are not the only factor causing delays in the recruitment process. It is also part of the company's strategic policy aimed at balancing cost efficiency with productivity.